Pengaruh Pelatihan dan Penempatan Kerja terhadap Kinerja Pegawai - Wisdalia Maya Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Every organizational system of government agencies in carrying out their activities will always try to achieve results in accordance with the objectives set. These objectives will not be realized without the active role of employees as one component of the organizational system. Employees have the main role in every organizational activity, because employees become planners, actors, and determinants of the realization of organizational system goals. In this case training and work placement. This study aims to find out: The effect of training on employee performance, The effect of employee work placement on employee performance, The effect of training and work placement of employees on the performance of the Lubuklinggau City Education Office. The data processing method is carried out with a saturated sampling approach, which is a sampling method whose entire population is used as a research sample. Data analysis carried out by validity and reliability test, normality test, classic assumption test, simple linear regression test, determination test, F test and T test. Based on the results of the research conducted, it can be concluded that Job Training and Placement significantly influence performance at the Lubuklinggau City Education Office. Keywords: Training, Job Placement, Employee Performance